The "brittle response" to Parkinson's disease medications: characterization and response to deep brain stimulation. - Daniel Martinez-Ramirez (Public Library of Science (PLoS), 2014)
Objective Formulate a definition and describe the clinical characteristics of PD patients with a "brittle response" (BR) to medications versus a "non-brittle response" (NBR), and characterize the use of DBS for this population. Methods An UF IRB approved protocol used a retrospective chart review of 400 consecutive PD patients presenting to the UF Center for Movement Disorders and Neurorestoration. Patient records were anonymized and de-identified prior to analysis. SPSS statistics were used to analyze data. Results Of 345 included patients, 19 (5.5%) met criteria for BR PD. The BR group was comprised of 58% females, compared to 29% in the NBR group (P = .008). The former had a mean age of 63.4 compared to 68.1 in the latter. BR patients had lower mean weight (63.5 vs. 79.6, P = <.001), longer mean disease duration (12.6 vs. 8.9 years, P = .003), and had been on LD for more years compared to NBR patients (9.8 vs. 5.9, P = .001). UPDRS motor scores were higher (40.4 vs. 30.0, P = .001) in BR patients. No differences were observed regarding the Schwab and England scale, PDQ-39, and BDI-II. Sixty-three percent of the BR group had undergone DBS surgery compared to 18% (P = .001). Dyskinesias were more common, severe, and more often painful (P = <.001) in the BR group. There was an overall positive benefit from DBS. Conclusion BR PD occurred more commonly in female patients with a low body weight. Patients with longer disease duration and longer duration of LD therapy were also at risk. The BR group responded well to DBS.